2009
DOI: 10.1007/s10722-009-9481-8
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite analysis of genetic diversity and population genetic structure of Aegilops tauschii Coss. in Northern Iran

Abstract: Genetic diversity and population genetic structure of Aegilops tauschii in Northern Iran were studied based on nine microsatellite loci. A high level of genetic diversity was observed from the accessions collected from six regions (provinces). These accessions include 79 samples of the two subspecies (tauschii and strangulata), the intermediate form (among morphologically distinguished subspecies) and ten accessions of Triticum aestivum. The nine microsatellites revealed a total of 141 alleles, with an average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Furthermore, as revealed by AMOVA, there is a higher level of genetic variation within species than among them, indicating a remarkable genetic diversity. Such a pattern of genetic diversity has been confirmed in many other crop wild relatives (Wolfe and Liston 1998;Deshpande et al 2001;Naghavi et al 2010;Saidi et al 2013). Therefore, the results of AMOVA supported genetic diversity within species which was obtained by cluster analysis.…”
Section: Diversity Analysis Using Issr Markersupporting
confidence: 69%
See 1 more Smart Citation
“…Furthermore, as revealed by AMOVA, there is a higher level of genetic variation within species than among them, indicating a remarkable genetic diversity. Such a pattern of genetic diversity has been confirmed in many other crop wild relatives (Wolfe and Liston 1998;Deshpande et al 2001;Naghavi et al 2010;Saidi et al 2013). Therefore, the results of AMOVA supported genetic diversity within species which was obtained by cluster analysis.…”
Section: Diversity Analysis Using Issr Markersupporting
confidence: 69%
“…The previous studies reported high levels of genetic diversity in Aegilops germplasm, especially in Ae. tauschii collected from different geographical origins of Iran by means of allozyms system (Dudnikov and Kawahara 2006), AFLP marker (Naghavi et al 2007), morphological characters (Aghaei et al 2008) and microsatellite marker (Naghavi et al 2010;Tahernezhad et al 2010). Table 1.…”
Section: Diversity Analysis Using Issr Markermentioning
confidence: 99%
“…Pour-Aboughadareh et al [ 61 ] using the ISSR technique revealed the high genetic diversity among Triticum boeoticum populations collected from different regions of Iran. Furthermore, Naghavi et al [ 62 ], Pour-Aboughadareh et al [ 63 ], Arabbeigi et al [ 28 ], and Etminan et al [ 64 ] reported a high level of genetic diversity among Iranian wild relatives of wheat using various markers such as ISSR, SSR, SCoT, and CBDP markers. As shown in Table 2 , the genetic diversity in the Ae.…”
Section: Discussionmentioning
confidence: 99%
“…They have been largely used in several species to assess genetic diversity and population structure (i.e. Mondini et al 2010;Asfaw et al 2009;Naghavi et al 2010). More recently, genetic diversity of the USDA (US Department of Agriculture) and CIP-FAO (International Potato Center) international nursery quinoa collection--which contains accessions from Peru, Bolivia, Ecuador, Argentina and Chile was assessed using SSR markers (Christensen et al 2007).…”
Section: Introductionmentioning
confidence: 99%